2004
DOI: 10.1063/1.1713045
|View full text |Cite
|
Sign up to set email alerts
|

Widely tunable terahertz-wave generation in an organic crystal and its spectroscopic application

Abstract: Terahertz (THz)-wave generation using difference-frequency mixing in an organic 4-N, N-dimethylamino-4′-N′-methyl-stilbazolium tosylate (DAST) crystal was investigated theoretically and experimentally. We developed a dual-wavelength optical parametric oscillator (OPO) with two KTiOPO4 crystals as the input light source. This oscillator has a tunable range from 1300–1450 nm and is pumped by a diode-pumped, frequency-doubled, Q-switched Nd:YAG laser with a pulse duration of 10 ns. Widely tunable THz waves rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(93 citation statements)
references
References 20 publications
2
85
0
Order By: Relevance
“…The lack of this absorption band in the case of the a-polarized pump might be due to a sharp reduction of spectral amplitudes for frequencies above ∼2 THz, as this reduction might eliminate the shallow and broad absorption. Thanks to the broad measurement bandwidth of our LAPC sensor, we can also identify a sharp and narrow resonance at ∼8.4 THz, which is very close to the previously reported 8.5-THz absorption of DAST by Taniuchi et al 74 who used DFG method to generate THz radiation. To understand the origination of the multiple resonances in organic crystals, rigid modeling work is needed.…”
Section: Zheng Et Alsupporting
confidence: 61%
“…The lack of this absorption band in the case of the a-polarized pump might be due to a sharp reduction of spectral amplitudes for frequencies above ∼2 THz, as this reduction might eliminate the shallow and broad absorption. Thanks to the broad measurement bandwidth of our LAPC sensor, we can also identify a sharp and narrow resonance at ∼8.4 THz, which is very close to the previously reported 8.5-THz absorption of DAST by Taniuchi et al 74 who used DFG method to generate THz radiation. To understand the origination of the multiple resonances in organic crystals, rigid modeling work is needed.…”
Section: Zheng Et Alsupporting
confidence: 61%
“…Terahertz waves were detected by a DTGS pyroelectric device at room temperature. Details of experimental setup have been reported elsewhere [11].…”
Section: Methodsmentioning
confidence: 99%
“…Later, difference frequency generation (DFG) was applied for tunable terahertz-wave generation from DAST [8]. In a series of our recent studies, we have found that tunable and coherent terahertz waves could be efficiently obtained by DFG when DAST was irradiated by two beams generated from a dual-wavelength OPO pumped by a nanosecond Nd:YAG SHG laser [9][10][11][12]. Frequencies from 0.3 to 3 THz were obtained by the two pumping wavelengths around 1000 nm while those from 2 to 30 THz were generated by the two beams from 1250 to 1550 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, 1-methyl-4-{2- [4-(dimethylamino)phenyl]ethenyl}-pyridinium p-toluenesulfonate (DAST: 2a in Fig. 1) [3][4][5] is one of the promising materials for this purpose [6][7][8][9], and the relevant studies on crystal growth, performance evaluation and device fabrication have extensively proceeded [10][11][12][13]. When DAST crystals are used as terahertzwave generators using difference frequency generation (DFG), polarized direction of the two laser beams with different wavelengths should be set parallel to crystallographic a-axis because diagonal component d 11 of DAST crystals is used.…”
Section: Introductionmentioning
confidence: 99%